Asilados ou exilados? : um estudo etnográfico com um grupo de idosos em Cuiabá, Mato Grosso - Bortoluzo, Renata Simone Vicente (2019)
This research seeks to understand the daily life of elderly residents of a Philanthropic Long Stay Institution in Cuiabá, Mato Grosso, through the description of sociabilities among the elderly and their peers and other agents. Specifically, the elderly perceptions about aging, as a social marker of difference, also their relation with gender, affectivity and family, in order to identify the meanings attributed by the elderly to the asylum experience. In this way, we seek to reflect critically on the negative stereotypes associated with Aging, as well as Institutionalization, in short, “how do the elderly feel in this institutional space?” Fieldwork took place from February to June 2018 and was carried out through participant observations. “Care” through different forms of “the gift” manifestations has proved to be a main factor for the maintenance of relationships in the asylum context insofar as it produces affection and improvement of health. Less than 10% of the elderly receive family visits. No hierarchy was observed regarding gender, but as regards age and shelter time. As a conclusion, according to most of the elderly interviewed, the Cuiabano Shelter represents a place where they feel less alone in both life and death. Some elderly people would like to return to their places of origin if they could take the life of before, however, deprived of health or financial conditions, conceive the shelter a place to live the last stage of life assured in needs such as food, care and safety.